614.8.084 METHODS OF EFFECTIVE ORGANIZATION OF FIRE AND RESCUE OPERATIONS - Egamberdiyev, Azizbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
Due to the impact of humanity’s technosphere and environment, the number of various types of emergencies is increasing. Among them, fires stand out due to the significant damage they cause. This is because such accidents and disasters negatively affect people’s lives and health, the property of legal and physical entities, as well as the environment, leading to the disruption of living conditions. This necessitates the implementation of measures to prevent fire-related emergencies and the use of effective methods in organizing firefighting operations to eliminate their consequences with minimal damage in case of occurrence. During the research, normative-legal documents, technical regulations, and standards were analyzed, as well as national experience studied, and recommendations for improving the firefighting operations organization system were developed.